Studying the effect of both airflow velocity and water flow velocity on heat exchange within a touring car cooler. - Myyasar Sheadah (Tishreen University, 2023)
Heat exchangers used in various industrial fields, including refrigeration devices and internal combustion engines, are exposed to heat losses associated with the heat transfer process, and to pressure losses that are indirectly associated with the rate of heat transfer, which leads to a decrease in the efficiency of the heat exchange process, which negatively affects the work of the exchanger. The proposed experimental and analytical study aims to study and test the Kia Rio passenger car cooler, including a complete modeling process for the cooler using the MATLAB program simulation process, which led to a high speed in data processing, conducting thermal calculations for the exchanger variables with high accuracy and speed, and drawing the curves of all the studied cases in addition to comparison of the analytical results with the experimental results made on the previous car cooler. The car radiator was also drawn with its dimensions using the solid program to be exported to the ansys program in order to calculate the values of other variables. The results of the previos study were compared with the results of the reference study and were superior to them by 10% for heat transfer coefficients.